Exploring the Relationship between Registration Flow and Patient Queues with the Quality of Outpatient Services at Kendari City Hospital - Sandi Arianti, Nelis; Tasnim, Tasnim; Himaniarwati, Himaniarwati (Waluya The International Science of Health Journal, 2025)
Introduction: Initial surveys show that health service procedures at the Hospital have met standard operating procedures but there are still many online queues, due to network constraints when inputting visits for both general patients and National Health Insurance, while offline queues such as patient queues that are piling up and crowded so that service time is still constrained. This attracted researchers to investigate the Relationship between Registration Flow and Patient Queues with the Quality of Outpatient Services at Kendari City Hospital. Method: The study used quantitative observational methods with a cross-sectional approach, the population was the number of outpatient visits at Kendari City Hospital from October to December 2023, which amounted to 34,304 visits with 96 samples, simple random sampling was used in drawing the samples. Result: Statistical test of service flow X2 count 14.096 > X2 table 3.841 Phi value = 0.408 and sig. value = 0.000 and service queue X2 count 24.690 > X2 table 3.841 Phi value = 0.531 and sig. value = 0.000 means there is a relationship between service flow and service queue to the service system in the outpatient unit of Kendari City Hospital. Conclusion: Increasing scientific knowledge in the field of public health, especially in providing information to the public through education regarding health services, in this case regarding service flows and patient queues.